Pengaruh Jumlah Tenaga Kerja Dan Kredit Perbankan Di Kalimantan Barat Tahun 1984-2013 - B01110102, JAINUDIN NAHUMARURY (Jurnal Curvanomic, 2016)
ABSTRACTThis study entitled "The Effect of Labor , Banking Credit Against Economic Growth InWest Kalimantan ". This study aims to determine how the influence of Labor and Economic Growthof Banking Credit for the period 1984-2013 in West Kalimantan .The method used in this research is quantitative descriptive method by using secondarydata, time series data , obtained from the office of the Central Bureau of Statistics and BankIndonesia West Kalimantan . The analytical tool used to process the data that is used Eviews 6Observations 30 years of data in the form of annual in West Kalimantan Province during the period1984 to 2013 .Multiple regression results of this study indicate that the variable Labor positive andsignificant impact on economic growth in West Kalimantan The higher the amount of Labor willencourage economic growth. Banking Credit variable and not significant positive effect , low lendingwill not boost economic growth. This is due to loan interest rates so high that the amount of lendingdeclined.Keywords : Labor, Banking Credit , Economic Growth .